2020
DOI: 10.1039/d0ce00724b
|View full text |Cite
|
Sign up to set email alerts
|

Same or different – that is the question: identification of crystal forms from crystal structure data

Abstract: The comparison of new structural data with crystal structures stored in the Cambridge Structural Database (CSD) is becoming ordinary when dealing with recognition and identification of new solid forms. Indeed,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 83 publications
3
39
0
Order By: Relevance
“…as temperature, can have an impact upon the geometric parameters defining weak, intermolecular interactions. 244,245 In this context and the above notwithstanding, it is worth mentioning a room temperature, variable-pressure study 246 of previously described 19, 88…”
Section: Crystengcomm Accepted Manuscriptmentioning
confidence: 91%
“…as temperature, can have an impact upon the geometric parameters defining weak, intermolecular interactions. 244,245 In this context and the above notwithstanding, it is worth mentioning a room temperature, variable-pressure study 246 of previously described 19, 88…”
Section: Crystengcomm Accepted Manuscriptmentioning
confidence: 91%
“…3) and of the crystal packing of TFA-IX with the CSD structures of tolfenamic acid (refcode family KAXXAI) confirmed that this crystal structure represents a true polymorph. 58 Detailed results of these comparisons can be found in the ESI. † Like all of the other eight polymorphs of this compound, the TFA molecules form R 2 2 (8) hydrogen-bonded dimers (Fig.…”
Section: Crystal Structure Of Tfa-ixmentioning
confidence: 99%
“…The availability of several series of isostructural crystals prompted an evaluation of the geometric parameters defining the X• • • X' interactions. The analysis was restricted to crystal structure determinations carried out under the same experimental conditions in order to ensure, as much as possible, a valid comparison between the derived data for each series [86,87].…”
Section: Relation To Congenersmentioning
confidence: 99%